ANALISIS KEMAMPUAN PSIKOMOTORIK DALAM PRAKTIKUM BIOKIMIA PERCOBAAN LIPID PADA MAHASISWA PROGRAM STUDI PENDIDIKAN KIMIA UNIVERSITAS MUHAMMADIYAH PONTIANAK - Atrisman Atrisman; Hairida Hadiarti; Fitriani Fitriani (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACTThis study aimed to describe the students’ psychomotor skills in Biochemistry Lab of Lipid Determination of Saponification Number in even semester in Academic Year 2014/2014. Using descriptive method, this study employed the entire students who took Biochemistry Lab course. The instruments used were observation and psychomotor-based interview. The study revealed that the students’ average score of each psychomotor aspect was 85.2%, the practical tool usage aspect was 83.93%, the practical tools stringing aspect was 92.56%, the experimental treatment observation aspect was 86.36%, and the phasic experimental performance aspect was 86.36%. As a result, it can be concluded that that the students of Chemistry Education have excellent psychomotor skills with the overall average score of psychomotor aspect of 86.27%.Keywords: descriptive, psychomotor skills, Biochemistry experimental